Adapt or die: how eukaryotic cells respond to prolonged activation of the spindle assembly checkpoint. (24th November 2010) - Rossio, Valentina; Galati, Elena; Piatti, Simonetta
Abstract : Many cancer-treating compounds used in chemotherapies, the so-called antimitotics, target the mitotic spindle. Spindle defects in turn trigger activation of the SAC (spindle assembly checkpoint), a surveillance mechanism that transiently arrests cells in mitosis to provide the time for error correction. When the SAC is satisfied, it is silenced. However, after a variable amount of time, cells escape from the mitotic arrest, even if the SAC is not satisfied, through a process called adaptation or mitotic slippage. Adaptation weakens the killing properties of antimitotics, ultimately giving rise to resistant cancer cells. We summarize here the mechanisms underlying this process and propose a strategy to identify the factors involved using budding yeast as a model system. Inhibition of factors involved in SAC adaptation could have important therapeutic applications by potentiating the ability of antimitotics to cause cell death.